Refractory spasms of focal onset—A potentially curable disease that should lead to rapid surgical evaluation. (October 2017) - Chipaux, Mathilde; Dorfmüller, Georg; Fohlen, Martine; Dorison, Nathalie; Metten, Marie-Astrid; Delalande, Olivier; Ferrand-Sorbets, Sarah; Taussig, Delphine
Highlights: Refractory spasms of focal onset should lead to rapid surgical evaluation. Spasms of focal onset have a similar postsurgical outcome as other seizure types. Volume and type but not topography of the lesion influence the age of onset. Normal MRI is rare so MRI is very helpful to locate the pathology in the pediatric population. Abstract: Purpose: Infantile spasms (IS) can occur as the only seizure type in children with surgically amenable epilepsies. Although early surgery has shown positive effects, little is known regarding outcomes. Methods: We retrospectively reviewed all children with IS referred to our tertiary center between 2002 and 2014 and try to define factors of outcome. Results: Sixty-eight children with focal onset seizures were referred: twenty children with a hemispheric implication and 48 with one or more lobes involved. The age of onset was significantly earlier in the hemispheric population (8.0 versus 16.7 months in the focal population). There was no difference in the age of onset between anterior and posterior onset zones, as we could expect regarding the maturation gradient. The epilepsy began earlier in life in tuberous sclerosis than in DNET. Only three children of the 48 non-hemispheric patients had a normal MRI at the time of the surgery. Temporal lobe was involved only in a third of the population. More than 86% of the patients were operated on. Patients with hemispheric lesions were operated on younger (2.6 years +/− 2.1 years) compared to 4.6 +/− 3.5 years in the whole population. The most frequent etiologies were in descending order: dysplasia, ganglioglioma or dysembryoplastic tumours and tuberous sclerosis. The global seizure outcome was favorable (Engel 1a) in 74.6% of the patients, and 87.9% if the delay between the first seizure and the surgery was less than 36 months. It fell to 64.7% if the delay exceeded 50 months. Conclusion: Spasms of focal onset have a similar postsurgical outcome as other seizure types so surgery may be an excellent option for treating selected patients with focal infantile spasms. Volume and type but not topography of the lesion influence the age of onset. MRI is very helpful to locate the pathology in the pediatric population, since only a small portion had a normal MRI.